The Impact of QRIS Adoption on Revenue Growth and Cost Efficiency of Micro and Small Enterprises in Yogyakarta: Evidence from a Panel Data Analysis - Ramadhan, Muhammad Fadhil; Salsabila, Dewi Kartika (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
This study investigates the impact of QRIS adoption on revenue growth and cost efficiency of micro and small enterprises in Yogyakarta using a panel data approach. Micro and small enterprises play a critical role in regional economic development, yet many still rely on conventional cash transactions. The introduction of QRIS as a standardized digital payment system aims to enhance transaction efficiency and financial inclusion. However, empirical evidence on its measurable economic impact at the firm level remains limited. This research employs a quantitative design using balanced panel data from 162 micro and small enterprises observed over a three year period from 2022 to 2024. The study applies Fixed Effects regression and Difference in Differences estimation to identify the causal impact of QRIS adoption on annual revenue growth and operational cost efficiency. Revenue growth is measured as the percentage increase in annual sales, while cost efficiency is proxied by the ratio of operational costs to revenue. The results indicate that QRIS adoption significantly increases annual revenue growth by approximately 6 to 7 percentage points. In addition, QRIS adoption significantly reduces operational cost ratios by about 5 percentage points, reflecting improved cost efficiency. The findings remain robust after controlling for firm age, firm size, and digital literacy. Digital literacy further strengthens performance outcomes, indicating that technological capability enhances the benefits of adoption. The study concludes that QRIS adoption contributes positively to financial performance and operational efficiency of micro and small enterprises in Yogyakarta. Digital payment integration functions not only as a transaction tool but also as a strategic instrument that supports productivity, competitiveness, and sustainable business growth.